2008
DOI: 10.1021/ol802334y
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Alkene Cross-Metathesis/Oxonium Ylide Formation−Rearrangement: Synthesis of the Anti-HIV Agent Hyperolactone C

Abstract: Alpha-diazo-beta-ketoesters bearing allylic ether functionality undergo highly stereoselective Ru-carbene-catalyzed alkene cross-metathesis followed by Rh(2)(OAc)(4)-catalyzed oxonium ylide formation/[2,3] sigmatropic rearrangement in a one-flask operation and in a highly diastereoselective manner. The methodology has been demonstrated in a concise synthesis of the anti-HIV agent hyperolactone C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…The (E)-enal 12 substrate for oxonium ylide formation-rearrangement had previously been prepared in 21 % yield from racemic diazo ether 10 by cross-metathesis using a large excess of methacrolein. [7] In the present study, ozonolysis followed by a Wittig olefination were found to give improved access to (E)-enal (R)-12 (66 % from diazo ether (R)-10, Scheme 7). The intermediate diazoaldehyde 25 was best obtained (88 %) after ozonolysis by using 1 equiv of PPh 3 (use of Me 2 S, or (MeO) 3 P were less satisfactory); the tolerance of the diazo group to this chemistry is noteworthy.…”
Section: Wwwchemeurjorgmentioning
confidence: 51%
See 2 more Smart Citations
“…The (E)-enal 12 substrate for oxonium ylide formation-rearrangement had previously been prepared in 21 % yield from racemic diazo ether 10 by cross-metathesis using a large excess of methacrolein. [7] In the present study, ozonolysis followed by a Wittig olefination were found to give improved access to (E)-enal (R)-12 (66 % from diazo ether (R)-10, Scheme 7). The intermediate diazoaldehyde 25 was best obtained (88 %) after ozonolysis by using 1 equiv of PPh 3 (use of Me 2 S, or (MeO) 3 P were less satisfactory); the tolerance of the diazo group to this chemistry is noteworthy.…”
Section: Wwwchemeurjorgmentioning
confidence: 51%
“…Racemic diazo ether 10 was originally prepared from a Lewis acid-catalysed Mukaiyama-type aldol reaction between [bisA C H T U N G T R E N N U N G (allyloxy)methyl]benzene and the silyl enol ether of ethyl diazoacetoacetate, [7] and for which there was no direct asymmetric version. [7] However, a potentially straightforward asymmetric synthesis of diazo ether 10 was considered that involved allylation of the precursor diazoalcohol 17 (Scheme 4), as this alcohol has previously been shown by Kundu and Doyle to be available for R = Me in 80 % yield and 95.5:4.5 e.r. by a catalytic asymmetric aldol reaction using benzaldehyde and the silyl enol ether of methyl a-diazoaceotacetate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[72] Ungesättigte 3-Oxo-2-diazocarbonsäureester wie 38 gehen in mäßigen bis guten Ausbeuten eine Ruthenium-katalysierte Olefin-Kreuzmetathese ein. [70,73] Dies ist insofern bemerkenswert, als derselbe Katalysator (Ruthenium-Carben-Komplex Grubbs II) Diazoessigester unter N 2 -Abspaltung in die entsprechenden Maleinsäureester (formale Carbendimere) umwandelt.…”
Section: Palladium-katalysierte Cc-verküpfung An Der Diazofunktionunclassified
“…[62] Acetessigester ( [64] In analoger Weise ließ sich Benzaldehyddiallylacetal als elektrophiler Reaktionspartner einsetzen. [70] Auch die Stereoselektivität der Aldol-Reaktionen war bereits ein Thema: Mit AgF/(R)-Binap als chiralem Katalysator konnte eine mäßige Enantioselektivität der Mukaiyama-Aldol-Reaktion von Diazoacetoacetaten erreicht werden. [67c] Hoch diastereoselektiv verlief hingegen die Addition des Lithiumenolats von 36 (R 1 = H, R 2 = Allyl) an chirale N-Sulfinylimine.…”
Section: Weitergehende Funktionalisierung Von Diazoverbindungenunclassified